2014
DOI: 10.1016/j.jascer.2014.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Morphology control of brushite prepared by aqueous solution synthesis

Abstract: Dicalcium phosphate dihydrate (DCPD, CaHPO 4 •2H 2 O), also known as brushite, is one of the important bioceramics due to not only diseases factors such as kidney stone and plaque formation but also purpose as fluoride insolubilization material. It is used medicinally to supply calcium, and is of interest for its unique properties in biological and pathological mineralization. It is important to control the crystal morphology of brushite since its chemical reactivity depends strongly on its surface properties;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 36 publications
(36 reference statements)
6
30
0
2
Order By: Relevance
“…the pH and reactant concentrations in a simplified aqueous solution process [29]. Consequently, the particle size and filterability of the sludge resulting from wastewater treatment with DCPD can likely be controlled by adjusting the morphology of DCPD during its manufacture.…”
Section: Resultsmentioning
confidence: 99%
“…the pH and reactant concentrations in a simplified aqueous solution process [29]. Consequently, the particle size and filterability of the sludge resulting from wastewater treatment with DCPD can likely be controlled by adjusting the morphology of DCPD during its manufacture.…”
Section: Resultsmentioning
confidence: 99%
“…In a subsequent step, crystal structure refinement has been performed. Indexation of the powder XRD data was confirmed for the unsubstituted brushite using the auto indexing program DIC VOL implemented in the FullProf program [43] as described in the experimental section. The present compound was confirmed to be single phased, all peaks being identified in the monoclinic struc ture of brushite.…”
Section: Unsubstituted Brushite Cahpo 4 2h 2 Omentioning
confidence: 99%
“…3) Research on controlling the morphology of DCPD particles has relevance for the aforementioned purposes, because their chemical reactivity and physical properties are determined by their surface condition, size, and shape. 4) In the case of solution synthesis, both Miller et al 5) and our group reported effective parameters for controlling the morphology of DCPD particles; examples include the initial pH value and concentration, 6) coexistence ions 7) and mixing process. 8) Modification of these parameters makes it possible to control the morphology of DCPD particles in terms of the tabular and petaloid shapes.…”
Section: Introductionmentioning
confidence: 91%